(untitled) (American Journal of Pedagogical and Educational Research, 2025)
The article describes a technique aimed at developing the coordination abilities of primary schoolchildren by circular training using sensitive periods of their physical development. This improved technique can be effectively used in physical education lessons and in sports sections for the development of coordination abilities of children.